1991
DOI: 10.1111/j.1471-4159.1991.tb02559.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Histamine in Rats with Hepatic Encephalopathy

Abstract: Chronic liver failure induced by portocaval anastomosis (PCA) in Wistar rats resulted in a dramatic increase in histamine concentration in hypothalamus and a smaller, but clearly pronounced, elevation in the rest of brain. Between 10 and 120 days following surgery, shunted rats exhibited a histamine level 2.4- to 13-fold higher in hypothalamus and 1.5- to 2.5-fold higher in the rest of brain as compared to their control, sham-operated pairs. There were no significant changes in histamine concentration in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 33 publications
(25 reference statements)
6
39
0
Order By: Relevance
“…PSE has been described as a disorder of multiple neurotransmitter systems. 13 Specifically, the histaminergic synaptic imbalance, which becomes apparent shortly 14,15 and persists for at least 8 months after surgery, 12,16-18 is among the most interesting consequences of portacaval shunting in the rat.We have previously shown that rats with PCA have profound disturbances in their brain histaminergic functions 6 months after surgery. 12,17,18 These rats have excessively high tissue levels of histamine in brain regions particularly enriched in histaminergic neurons and/or cell bodies.…”
mentioning
confidence: 99%
“…PSE has been described as a disorder of multiple neurotransmitter systems. 13 Specifically, the histaminergic synaptic imbalance, which becomes apparent shortly 14,15 and persists for at least 8 months after surgery, 12,16-18 is among the most interesting consequences of portacaval shunting in the rat.We have previously shown that rats with PCA have profound disturbances in their brain histaminergic functions 6 months after surgery. 12,17,18 These rats have excessively high tissue levels of histamine in brain regions particularly enriched in histaminergic neurons and/or cell bodies.…”
mentioning
confidence: 99%
“…PCA, 12,14,15,25 and the observation of significantly increased extracellular levels of histamine, 37 it appears that the altered sleep patterns during the light phase in rats with PCA mirror the changes in the brain histaminergic system. Therefore, we suggest that, in addition to other factors, histamine may play a role in the development of sleep disturbances in rats with PCA.…”
Section: Fig 4 (A)mentioning
confidence: 95%
“…9,11 One of the most striking consequences of the PCA surgery in rats is the remarkable elevation of brain histamine levels, which appears as early as 10 days, and persists for at least 8 months after PCA surgery. [12][13][14][15] The significance of this observation for the pathogenesis of PSE, however, has not been studied in detail.Histaminergic neurons in the mammalian brain are thought to play a role in the control of vigilance, sleep, and wakefulness, [16][17][18][19][20][21] and in the modulation of circadian rhythmicity. 22 The role of histaminergic mechanisms in the control of the sleep-wakefulness continuum in humans has also been confirmed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to transient changes of histaminergic activity induced by thioperamide, the portocaval anastomosis (PCA) operation of the liver not only permanently elevates the brain histamine level (Fogel et al, 1991(Fogel et al, , 1994Imura et al, 1986;Lozeva et al, 1995; but also permanently renders animals more liable to release histamine by thioperamide (Anttila et al, 1995). Hence, those plausible histaminergic modes of actions described above were examined both in unoperated controls and in PCA-operated rats.…”
Section: Introductionmentioning
confidence: 99%